Implementasi Nilai-Nilai Pendidikan Islam Dalam Surah As-Saffat Ayat 102 - Alimul Muniroh (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2018)
The purpose of this paper is to know (1) the values ​​of Islamic education contained in the verse as-saffat verse 102, and (2) the implementation of Islamic educational values ​​contained in the verse as-saffat verse 102 in class learning. This research type is library research with descriptive qualitative approach. The method in this study is explorative, namely to find the meaning of the value of education contained in surah as-saffat verse 102 from various books of interpretation which is the interpretation of mufassir in understanding the meaning, contents and content contained in the verse. Includes the book of tafsir: the book of tafsir al-Misbah by M.Quraish Shihab, the Ibn Katsir interpretation of the book by Sheikh Ismail bin Katsir, and the book of tafsir al-Maraghi by Ahmad Musthofa al-Maraghi. The results of the study show that the values ​​of Islamic education contained in surah as-saffat verse 102 are (1) the education of ketauhidan (akidah), (2) education of democratic consultation (syari'ah), and (3) moral education. And it shows that the concept of learning in the verse as-saffat verse 102 through the story of Abraham and Prophet Ismail consists of: (1) Educational objectives: humanization, humanity, noble character, (2) Material: akidah, syari'ah and akhlak, ( 3) Educators: wise, loving, democratic, acquainted with the students and understanding their psychology, understanding material, patience and sincerity, (4) Adolescents: obedient, patient, desirous or ideals, teachers, (5) Methods: dialogue-democratic, have been implemented in classroom learning.